2013
DOI: 10.9758/cpn.2013.11.2.80
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Metabolic Syndrome in Schizophrenic Patients Using Antipsychotics

Abstract: Objective: To examine the prevalence of metabolic syndrome and its risk factors in a large group of schizophrenic patients. Methods: Sociodemographic and treatment data were collected from medical records of 1,103 inpatients and outpatients treated for schizophrenia at Seoul National Hospital in Seoul, Korea. Anthropometric measurement and blood testing were conducted for collection of physical and biochemical data and diagnosis of metabolic syndrome. Data for metabolic syndrome prevalence were compared by sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 24 publications
3
22
2
7
Order By: Relevance
“…Previous data demonstrated the role of glucose administration in attenuating deficits in verbal declarative memory [22] in agreement with other studies demonstrating a relation between glucose regulation and memory performance [22,23]. Those suffering from schizophrenia have a tendency to develop the metabolic syndrome, which comprises type 2 diabetes mellitus, dyslipidemia and hypertension, all representing medical conditions that increase intra-abdominal fat deposition and are in a way also controlled by cortisol levels [24]. Evidence indicates that drug-naïve or drug-free schizophrenia patients present higher levels of plasma cortisol, which indicates an imbalance in the hypothalamic-pituitary-adrenal axis and also increased levels of corticotropin-releasing hormone in CSF samples [25]; however, some other studies do not show significant increases in cortisol levels [26].…”
Section: Glycolysis Pathway and Oxidative Stresssupporting
confidence: 86%
“…Previous data demonstrated the role of glucose administration in attenuating deficits in verbal declarative memory [22] in agreement with other studies demonstrating a relation between glucose regulation and memory performance [22,23]. Those suffering from schizophrenia have a tendency to develop the metabolic syndrome, which comprises type 2 diabetes mellitus, dyslipidemia and hypertension, all representing medical conditions that increase intra-abdominal fat deposition and are in a way also controlled by cortisol levels [24]. Evidence indicates that drug-naïve or drug-free schizophrenia patients present higher levels of plasma cortisol, which indicates an imbalance in the hypothalamic-pituitary-adrenal axis and also increased levels of corticotropin-releasing hormone in CSF samples [25]; however, some other studies do not show significant increases in cortisol levels [26].…”
Section: Glycolysis Pathway and Oxidative Stresssupporting
confidence: 86%
“…They are rapidly becoming a favorite first choice for this indication, mainly due to their low propensity to cause extrapyramidal adverse effects and favorable efficacy in ameliorating both positive and negative symptoms 1). Some studies have, however, shown that these novel compounds are associated with metabolic abnormalities characterized by hyperglycemia, dyslipidemia, and an increased risk of diabetes mellitus 2,3). Metabolic syndrome is characterized by the symptoms of central obesity, insulin resistance, atherogenic dyslipidemia, hypertension, ischemic heart disease (IHD), and overall mortality 4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, vulnerability factors for development of schizophrenia, diabetes, and MetS seem to be shared and interconnected. In patients with schizophrenia the risk is further greatly increased by the use of antipsychotic medication as reviewed repeatedly elsewhere 8,[51][52][53][54][55] . More specifically, elevated blood levels of adiponectin have been reported in schizophrenia 56 and there is a correlation between serum leptin levels and body weight 51 .…”
Section: Psychiatric Disorders and Metabolic Syndromementioning
confidence: 99%